Predicting the rutting behaviour of natural fibre-reinforced cold mix asphalt using the finite element method. (10th April 2018) - Shanbara, Hayder Kamil; Ruddock, Felicite; Atherton, William
Highlights: Cold mix asphalt mixtures reinforced using natural fibres. Modelling rutting phenomena of new CMA mixtures. Model can properly predict rutting of reinforced and unreinforced CMA mixtures. CMA quality is an important factor to reduce rutting within layer depth. Results show that natural fibre has positive effects on rutting behaviour of CMA. Abstract: This paper describes the development of a three-dimensional (3-D), finite element model (FEM) of flexible pavements made with cold mix asphalt (CMA), which has itself been reinforced with two different natural fibres: jute and coir. A 3-D finite element model was employed to predict the viscoelastic response of flexible CMA pavements when subjected to multiple axle loads, different bituminous material properties, tire speeds and temperatures. The analysis was conducted by the finite element computer package ABAQUS/STANDARD. The pavements were subject to cyclic and static loading conditions to test for permanent deformation (rutting). The accuracy of the developed model was validated by comparing the predicted results with those measured in the lab. Reinforced and unreinforced CMA mixture models were simulated in this research. The results indicate that the CMA mixtures reinforced with natural fibres, are effective in mitigating permanent deformation (rutting). These reinforcing materials can extend the service life of flexible pavements.